2009
DOI: 10.1007/s11999-009-0912-9
|View full text |Cite
|
Sign up to set email alerts
|

Early Equivalence of Uncemented Press-fit and Compress® Femoral Fixation

Abstract: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
75
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 34 publications
11
75
1
1
Order By: Relevance
“…We believe these data support the potential long-term durability of an osteointegrated CPS implant. Aseptic mechanical failures occurred early, within 1 year of revision surgery, a finding comparable to other primary CPS implant studies [10,13,19,24]. Few publications have described the outcomes of revision distal femoral prostheses (Table 2).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We believe these data support the potential long-term durability of an osteointegrated CPS implant. Aseptic mechanical failures occurred early, within 1 year of revision surgery, a finding comparable to other primary CPS implant studies [10,13,19,24]. Few publications have described the outcomes of revision distal femoral prostheses (Table 2).…”
Section: Discussionsupporting
confidence: 74%
“…The CPS implant has a published survival rate of as high as 89% at 5 years [19] and 80% at 10 years [13] when used for primary oncologic reconstruction [24]. In short-term comparison studies, it was shown to have equivalent or higher survival than cemented [3,24] and press-fit [10] stemmed implants for primary oncologic reconstruction [3,24]. Given the versatility of the CPS implant, we began using it for revision of failed distal femoral prostheses, particularly when the residual femoral bone segment was very short, precluding use of a stemmed implant.…”
Section: Introductionmentioning
confidence: 99%
“…Loading forces are transmitted directly onto the host bone in an axial direction resulting in bone growth at the boneprosthesis interface and osseointegration ( Fig. 1) [1,8,15]. This device has short-and intermediate-term survivorship that is at least equivalent if not superior to stemmed implants, but there is concern that rotational forces at the bone-prosthesis interface can lead to loosening and failure of the implant (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This device has short-and intermediate-term survivorship that is at least equivalent if not superior to stemmed implants, but there is concern that rotational forces at the bone-prosthesis interface can lead to loosening and failure of the implant (Fig. 2) [3,8,17]. A strategy to overcome this problem is to insert antirotation pins through the spindle into the host bone (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation